Analysis of the impact of human capital in raising the level of financial performance: Al-Janoob Islamic Bank as a model - Muaamal Hussein Jwesim; Ghufran shallal mohammed (International Journal of Economics, Commerce, and Management, 2024)
In light of the increasing degree of competition in the international business environment resulting from the technological changes that have occurred recently, which has made companies rely on elements through which they can increase the companies’ capabilities to compete and achieve what they aim for, and for this reason the human element (human capital) was the factor. It is decisive in increasing productivity and companies’ abilities to compete in light of the changing and evolving business environment, as the research showed that there is a major role for human capital in increasing the financial performance of the research sample (Al-Janoob Islamic Bank) and achieving high profit levels as a result of that company’s acquisition of competent and skilled human capital. The research compared two different periods in terms of the company’s management at the levels of executive management and the board of directors, and after the bank applied governance and separated ownership of the institution from management, and competent banking and professional cadres took over the management of that company, which was characterized by efficiency and effectiveness, as the research showed the existence of a close and strong relationship between human capital. Efficiency and financial performance represented by the profitability index, where the level of profits achieved before the change of management was low, while it took an upward trend gradually after the change of management and the application of governance. This confirms the relationship between two variables in achieving what the institution aims to achieve in its current and future strategies.